Lack of durable protection against cotton smoke‐induced acute lung injury in sheep by nebulized single chain urokinase plasminogen activator or tissue plasminogen activator. Issue 1 (18th June 2018) - Fukuda, Satoshi; Enkhbaatar, Perenlei; Nelson, Christina; Cox, Robert A.; Wolfson, Marla R.; Shaffer, Thomas H.; Williams, Robert O.; Surasarang, Soraya Hengsawas; Sawittree, Sahakijpijarn; Florova, Galina; Komissarov, Andrey A.; Koenig, Kathleen; et al.
Abstract: Background: Airway fibrin casts are clinically important complications of severe inhalational smoke‐induced acute lung injury (ISIALI) for which reliable evidence‐based therapy is lacking. Nebulized anticoagulants or a tissue plasminogen activator; tPA, has been advocated, but airway bleeding is a known and lethal potential complication. We posited that nebulized delivery of single chain urokinase plasminogen activator, scuPA, is well‐tolerated and improves physiologic outcomes in ISIALI. To test this hypothesis, we nebulized scuPA or tPA and delivered these agents every 4 h to sheep with cotton smoke induced ISIALI that were ventilated by either adaptive pressure ventilation/controlled mandatory ventilation (APVcmv; Group 1, n = 14) or synchronized controlled mandatory ventilation (SCMV)/limited suctioning; Group 2, n = 32). Physiologic readouts of acute lung injury included arterial blood gas analyses, PaO2 /FiO2 ratios, peak and plateau airway pressures, lung resistance and static lung compliance. Lung injury was further assessed by histologic scoring. Biochemical analyses included determination of antigenic and enzymographic uPA and tPA levels, plasminogen activator and plasminogen activator inhibitor‐1 activities and d ‐dimer in bronchoalveolar lavage (BAL). Plasma levels of uPA, tPA antigens, d ‐dimers and α‐macroglobulin‐uPA complex levels were also assessed. Results: In Group 1, tPA at the 2 mg dose was ineffective, but at 4 mg tPA or scuPA, the PaO2 /FiO2 ratios, peak/plateau pressures improved during evolving injury (p < 0.01) without significant differences at 48 h. To improve delivery of the interventions, the experiments were repeated in Group 2 with limited suctioning/SCMV, which generally increased PAs in (BAL). In Group 2, tPA was ineffective, but scuPA (4 or 8 mg) improved physiologic outcomes (p < 0.01) and plateau pressures remained lower at 48 h. Airway bleeding occurred at 8 mg tPA. BAL plasminogen activator (PA) levels positively correlated with physiologic outcomes at 48 h. Conclusions: Physiologic outcomes improved in sheep in which better delivery of the PAs occurred. The benefits of nebulized scuPA were achieved without airway bleeding associated with tPA, but were transient and largely abrogated at 48 h, in part attributable to the progression and severity of ISIALI.